(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article is devoted to synthesis of the low-frequency vibration exciter for checking of sensors of acceleration. In many areas of the modern equipment sensors of acceleration working in very low range of frequencies are widely used. For checking and graduation of such sensors the vibration exciter capable to provide rectilinear horizontal harmonic oscillations of the calibrated accelerometer in so low range of frequencies are required. Low frequencies of fluctuations cause the necessity of creation of big amplitudes of movements for ensuring the acceptable values of amplitudes of accelerations. The low-frequency electrodynamic vibration exciter with a magnetic suspension of mobile part which is a component of the National Standard of the vibration movement of the Russian Federation is so far created. However, development of the modern equipment demands expansion of frequency ranges to the area of ultralow frequencies. One of requirements shown to the vibration exciter working in the ultralow range of frequencies is increase in amplitude of horizontal movements of a mobile part as with small amplitudes the speed and acceleration of the harmonious law of the movements proportional according to the frequency of fluctuations and a square of this frequency, will have small amplitude values. One of problems of realization of a control system of the electric drive of the vibration exciter consists in that a mobile part possesses indifferent position of balance. The centre of fluctuations of a mobile part is not defined and can be in any point on magnetic conductor length. That fluctuations had the steady centre in an average point of a magnetic conductor without use of a mechanical spring, the drive is supplied with an additional control system of fluctuations, or a so-called electromagnetic spring.